PEMAHAMAN HAKIM MAHKAMAH SYAR’IYAH KUALA SIMPANG DALAM MENYELESAIKAN SENGKETA EKONOMI SYARIAH - Zaharullah Zaharullah (SYARIAH: Journal of Islamic Law, 2023)
to Law no. 7 of 1989 concerning religious courts. And the Qanun of Nanggroe Aceh Darussalam Province Number 10 of 2002 Concerning Islamic Sharia Courts, has brought a number of fundamental changes to the environment, especially in the settlement of disputes in the religious courts, so that with the enactment of Law no. 3 of 2006, and the Qanun of Nanggroe Aceh Darussalam Province Number 10 of 2002. The authority of the syar'iyah court, in addition to covering cases in the fields of marriage, inheritance, wills, grants, waqf, and alms, also includes cases in the fields of Zakat, infaq and sharia economics. Even though sharia economic dispute cases are new cases within the Syar'iyah court environment, the Kuala Simpang Syar'iyah Court judges already have competence in resolving sharia economic dispute cases.